Vision-based Assembly and Inspection System for Golf Club Heads. (April 2015) - Natsagdorj, Sainbuyan; Chiang, John Y.; Su, Che-Han; Lin, Chih-chung; Chen, Cheng-yen
Abstract: Golf club head production is started by creating metallic films and forming blank casts, which then undergo complex and sophisticated assembly procedures, morphological inspection and strength testing. Not only chemicals used in these processes often threaten the health of operators, but also most of this backend processing involves manual assembly and welding, demanding substantial amounts of manpower. In light of these pitfalls, this paper proposes a Vision-based Assembly and Inspection System for Golf Club Heads (VAIS-GCH) to mitigate the time-consuming and labor-intensive golf club head production process. Two cameras are coordinated to capture top-view image of the striking plate, and top- and side-views of the casting body for visual processing. After the barycenter shift and shifting angle of the striking plate are determined, a robot arm is then directed to suction up the striking plate from the conveyor belt, adjust it to the canonical orientation, and move the yet-to-be assembled striking plate to the top of the casting body. The 3D spatial positions of the casting body, namely, the XYZ shifting angles of the coupling opening, are detected by comparing the top- and side-view images captured with pre-stored 3D golf club head template to facilitate the coupling of the striking plate and casting body. The side-view camera monitors the insertion depth of the striking plate during the coupling process to make sure the surface of the striking plate levels with the casting body. The loft angle, formed by the line perpendicular to the tangent of the bottom of casting body and the tangent of the striking surface, is tested to confirm whether specifications are satisfied. Through the coordination of two cameras, the accuracy and efficiency of the golf club head assembly are increased significantly. The alignment error is smaller than 0.8 mm and the assembly and inspection process takes less than 2 s. Highlights: This study presents a Vision-based Assembly and Inspection System for Golf Club Heads (VAIS-GCH). Ths system adopts automated mechanical arms matched with cameras for 3D space alignment. Through the coordination of two cameras, the accuracy of the golf club head assembly is increased significantly.